GABUNGAN KEPEMIMPINAN KENABIAN (LI) DENGAN KEPEMIMPINAN KI HAJAR DEWANTARA (L2) UNTUK MENINGKATKAN HASIL REFORMASI BIROKRASI - Nugroho, Dwi; Rachman, Abdul (BEduManagers Journal : Borneo Educational Management and Research Journal, 2021)
The combined of prophetic leadership and trilogy leadership concepts called as neo- prophetic leadership. The neo-prophetic leadership covers prophets characteristics and Dewantara’steachings. The combining two leaderships models -then become L1L2- is believed able to increaseresult of bureaucratic reformation. The combination referred to descriptive and prescriptive theorieswhich were developed from theoretical and empirical perspectives. In this writing, L1 as a symbol of Prophetic Leadership, and L2 as a symbol of Dewantara’s Leadership which he is abringer of leadership trilogy teachings. This is a leadership prescription that derived from eternaluniversal values-prophetic- while still maintaining local wisdom values -trilogy- which itseffectiveness detail explained descriptively. L1L2 need to be tested by leaders and placed theorganization as a laboratoryto try-out it.